Global sporting events : battlegrounds for human rights - Dorsey, James M. (2012)
With the London Olympics less than two months away major global sporting events are increasingly proving to be Middle Eastern battlegrounds for human rights rather than an expensive way for countries to boost their prestige and sense of national pride.